Duplex stainless steel wire rod and duplex stainless steel wire
Patent Information
- Application Number
- JP2023511340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-29
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2042-03-29
AI Technical Summary
【0015】 本発明によれば、製造性を確保しながらも、ノズル閉塞を抑制することができ、かつ良好な熱間加工性と溶接作業性とを有する二相ステンレス鋼線材を得ることができる。
Smart Images

Figure 0007636522000001 
Figure 0007636522000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a duplex stainless steel wire rod and a duplex stainless steel wire. [Background technology]
[0002] Duplex stainless steel may be welded for use depending on the application. There are various welding methods, but when welding duplex stainless steel, for example, gas metal arc welding (also called GMA welding) may be used.
[0003] The GMA welding method is a welding method in which a welding material such as a welding rod (welding wire) is used as an electrode, and a weld metal is formed by the molten welding material and the molten base metal. In this case, duplex stainless steel is usually used as the welding material.
[0004] In the manufacturing process, duplex stainless steel for welding materials needs to be processed to reduce the wire diameter. Therefore, good hot workability is required. In order to improve hot workability, it is necessary to thoroughly deoxidize and desulfurize the steel to reduce the S concentration in the steel. For this reason, Al is used for deoxidization.
[0005] On the other hand, when deoxidization is performed with Al, MgO·Al2O3 spinel is likely to form as an inclusion. This MgO·Al2O3 spinel coarsens in the submerged entry nozzle during continuous casting, easily causing nozzle clogging and reducing manufacturability. For this reason, it is effective to add Ca to suppress the formation of MgO·Al2O3 spinel. On the other hand, if Ca is added to duplex stainless steel for welding materials, it will cause spattering, which causes metal particles and slag to fly off, reducing welding workability.
[0006] In view of this, Patent Document 1 discloses a duplex stainless steel in which the Ca content, ferrite phase ratio, inclusion composition, etc. in the steel are controlled to suppress the formation of MgO·Al2O3 spinel and to suppress nozzle clogging, etc., while ensuring hot workability and weldability. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-171640 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, in the duplex stainless steel disclosed in Patent Document 1, the range of the Ca content is specified to be very narrow in order to ensure hot workability and welding workability while suppressing nozzle clogging and the like. Therefore, in actual operation, the load for adjusting the chemical composition is large, and manufacturability may decrease. In addition, from the viewpoint of composition, there is room for further improvement in nozzle clogging. Therefore, there is a problem that it is difficult to suppress nozzle clogging while ensuring manufacturability, and to simultaneously achieve good hot workability and welding workability.
[0009] An object of the present invention is to solve the above problems and to provide a duplex stainless steel wire rod that can suppress nozzle clogging while ensuring manufacturability and has good hot workability and welding workability. [Means for solving the problem]
[0010] The present invention has been made to solve the above problems, and the gist of the present invention is the following duplex stainless steel wire rod.
[0011] (1) A duplex stainless steel wire rod having inclusions with a major axis of 1 μm or more and containing one or more selected from S and O, Chemical composition, in mass%, C: 0.005-0.10%, Si: 0.2-2.0%, Mn: 6.0% or less, P: 0.04% or less, S: 0.0050% or less, Ni: 2.0-14.0%, Cr: 18.0-28.0%, Mo: 0.05-5.50%, Cu: 2.0% or less, N: 0.10-0.35%, O: 0.0001 to 0.0060%, Al: 0.010-0.2%, Ca: 0.0025% or less, Mg: 0.0100% or less, REM: 0~0.01%, Ta: 0 to 0.10%, B: 0~0.0020%, W: 0-2.0%, V: 0~1.00%, Ti: 0 to 0.005%, Nb: 0-0.10%, Sn: 0~0.10%, Sb: 0-0.30%, Co: 0-1.00%, Zr: 0 to 0.0050%, Ga: 0 to 0.01%, The balance is Fe and impurities. The DF value calculated by the following formula (i) is 20 to 60%, When oxides containing CaO, Al2O3, and MgO, the total of which satisfies the following formula (ii) and the ratio of Al2O3 to MgO satisfies the following formula (iii) are defined as Ca-Al-Mg-based oxides among the inclusions, A duplex stainless steel wire rod, wherein the ratio of the number of the Ca-Al-Mg-based oxides to the number of the inclusions is 75% or more. DF value=7.2×(Cr+0.88Mo+0.78Si+2.2Ti+2.3V)-8.9×(Ni+0.03Mn+0.72Cu+22C+21N)-44.9 (i) CaO+Al2O3+MgO+ROx+Ta2O5≧90% (ii) Al2O3 / MgO≦1.25 (iii) In formula (i), each element symbol represents the content (mass%) of each element in the steel, and if the element is not present, it is set to zero. In formula (ii), ROx represents REM oxides, and in formulas (ii) and (iii), CaO, Al2O3, MgO, ROx, and Ta2O5 represent the mass% of each oxide, and if the element is not present, it is set to zero.
[0012] (2) The chemical composition is, in mass%, REM: 0.0005~0.01%, Ta: 0.001 to 0.10%, B: 0.0001~0.0020%, W: 0.05-2.0%, V: 0.01 to 1.00%, Ti: 0.001 to 0.005%, Nb: 0.02 to 0.10%, Sn: 0.02-0.10%, Sb: 0.01 to 0.30%, Co: 0.07 to 1.00%, Zr: 0.0001 to 0.0050%, and Ga: 0.0001 to 0.01%, The duplex stainless steel wire rod according to the above (1), comprising one or more selected from the following:
[0013] (3) The duplex stainless steel wire rod according to (1) or (2) above, which is used as a welding material.
[0014] (4) A duplex stainless steel wire using the duplex stainless steel wire material according to (1) or (2) above. Effect of the Invention
[0015] According to the present invention, it is possible to obtain a duplex stainless steel wire rod that can suppress nozzle clogging while ensuring manufacturability and has good hot workability and welding workability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present inventors have conducted research into duplex stainless steel wire rods suitable for use as welding materials and have obtained the following findings (a) to (c).
[0017] (a) When deoxidizing with Al to ensure hot workability, MgO·Al2O3 spinel is formed, causing nozzle clogging. Adding Ca is effective in suppressing the formation of this MgO·Al2O3 spinel, but the inclusion of Ca makes spatter more likely to occur, reducing welding workability.
[0018] (b) Therefore, the inventors investigated whether the formation of MgO·Al2O3 spinel could be suppressed by methods other than increasing the Ca content. As a result, they found that by increasing the activity of MgO in the slag and decreasing the activity of Al2O3, MgO, rather than MgO·Al2O3 spinel, was formed preferentially.
[0019] (c) The formation of MgO suppresses nozzle clogging and ensures hot workability and weldability. In addition, it is not necessary to control the Ca content within a very strict range, which is also effective in practical operation.
[0020] An embodiment of the present invention has been made based on the above findings. Each requirement of this embodiment will be described in detail below.
[0021] 1. Chemical composition of duplex stainless steel wire The reasons for limiting the content of each element in the duplex stainless steel wire rod are as follows. In the following description, "%" for the content means "mass %".
[0022] C: 0.005 to 0.10% C (carbon) is an impurity present in steel and is also a strong austenite-forming element. If the C content is low, the DF value described below will drop significantly. For this reason, the C content is set to 0.005% or more, preferably 0.010% or more, and more preferably 0.015% or more. However, if C is included in excess, it will combine with Cr during welding and welding reheating to form carbides. As a result, the toughness and corrosion resistance of the weld metal will decrease. For this reason, the C content is set to 0.10% or less. The C content is set to 0.08% or less, and more preferably 0.025% or less.
[0023] Silicon: 0.2 to 2.0% Silicon (Si) is an element that acts as a deoxidizer when duplex stainless steel is melted. For this reason, the Si content is set to 0.2% or more. The Si content is preferably set to 0.3% or more, more preferably set to 0.35% or more, and even more preferably set to 0.4% or more. However, if an excessive amount of Si is contained, the hot workability decreases. For this reason, the Si content is set to 2.0% or less. The Si content is preferably set to 1.2% or less, and even more preferably set to 1.0% or less. the following It is more preferable to keep it at 0.6% or less, and further more preferable to keep it at 0.6% or less.
[0024] Mn: 6.0% or less Mn (manganese) is a deoxidizing agent and has the effect of improving hot workability by fixing S as MnS. It is also an element that acts to stabilize austenite and has the effect of controlling the DF value described later. However, excessive Mn content leads to refractory erosion during melting and a decrease in the corrosion resistance of the product. For this reason, the Mn content is set to 6.0% or less. The Mn content is preferably set to 5.0% or less, more preferably set to 2.0% or less, and even more preferably set to 1.0% or less. On the other hand, in order to obtain the above effect, the Mn content is preferably set to 0.5% or more, and more preferably set to 0.7% or more.
[0025] P:0.04% or less P (phosphorus) is an impurity element contained in steel, which reduces toughness, hot workability, and corrosion resistance. For this reason, the P content is set to 0.04% or less, and preferably 0.03% or less. It is preferable to reduce P as much as possible, but excessive reduction increases the load during refining and increases raw material costs. For this reason, the P content is preferably set to 0.005% or more.
[0026] S: 0.0050% or less S (sulfur) is an impurity element contained in steel, and reduces toughness, hot workability, and corrosion resistance. For this reason, the S content is set to 0.0050% or less, and preferably 0.0025% or less. It is preferable to reduce S as much as possible, but excessive reduction increases the load during refining and increases raw material costs. For this reason, the S content is preferably set to 0.0002% or more.
[0027] Ni: 2.0-14.0% Ni (nickel) is an element that contributes to the stabilization of austenite. It also has the effect of improving the corrosion resistance and toughness of the weld metal and suppressing hot working cracks. For this reason, the Ni content is set to 2.0% or more. The Ni content is preferably set to 4.0% or more, and more preferably set to 6.0% or more. However, Ni is an expensive element, and excessive inclusion of Ni leads to increased costs. For this reason, the Ni content is set to 14.0% or less. The Ni content is preferably set to 12.0% or less, and more preferably set to 11.0% or less.
[0028] Cr: 18.0~28.0% Cr (chromium) is a basic element of stainless steel and contributes to improving the corrosion resistance of the weld metal. For this reason, the Cr content is set to 18.0% or more. The Cr content is preferably set to 20.0% or more, more preferably set to 22.0% or more, and even more preferably set to 24.0% or more. However, Cr promotes the formation of σ phase in the welded zone and reduces the toughness of the welded zone. For this reason, the Cr content is set to 28.0% or less. The Cr content is preferably set to 27.0% or less.
[0029] Mo: 0.05 to 5.50% Mo (molybdenum) is an element effective in improving corrosion resistance. It also has the effect of improving strength by solid solution strengthening. For this reason, the Mo content is set to 0.05% or more. The Mo content is preferably set to 0.10% or more, more preferably set to 3.00% or more, and even more preferably set to more than 4.00%. However, if Mo is contained excessively, hot workability is reduced. For this reason, the Mo content is set to 5.50% or less, and preferably set to 4.50% or less.
[0030] Cu:2.0% or less Cu (copper) is an element that contributes to the stabilization of austenite, but if it is contained in excess, hot workability is reduced. Therefore, the Cu content is set to 2.0% or less, and preferably 1.0% or less. On the other hand, in order to obtain the above effect, the Cu content is preferably set to 0.05% or more, more preferably 0.5% or more, and even more preferably more than 0.5%.
[0031] N: 0.10~0.35% N (nitrogen) is an element that contributes to the stabilization of austenite. In addition, N has the effect of improving corrosion resistance and strength. For this reason, the N content is set to 0.10% or more, and preferably 0.20% or more. However, excessive N content may cause surface defects due to a decrease in hot workability. For this reason, the N content is set to 0.35% or less, and preferably 0.30% or less.
[0032] O: 0.0001 to 0.0060% O (oxygen) is the main element contained in inclusions that cause nozzle clogging. In addition, the lower the O concentration in steel, the higher the solubility of Mg, so it is desirable to reduce the O content. For this reason, the O content is set to 0.0060% or less. The O content is preferably set to 0.0030% or less, and more preferably set to 0.0015% or less. It is preferable to reduce O as much as possible, but excessive reduction increases the load during refining. For this reason, the O content is set to 0.0001% or more.
[0033] Al: 0.010~0.2% Al (aluminum) has the effect of deoxidizing steel. Furthermore, if deoxidation is insufficient, desulfurization does not proceed, which leads to rusting originating from sulfides and a decrease in hot workability. Appropriate deoxidation is also important for reducing MgO in the slag to increase the Mg concentration in the molten steel and control inclusions to a high MgO concentration. For this reason, the Al content is set to 0.010% or more. However, excessive Al content reduces workability. Therefore, the Al content is set to 0.2% or less, and preferably 0.12% or less.
[0034] Ca: 0.0025% or less Ca (calcium) has the effect of suppressing the generation of MgO·Al2O3 spinel that causes nozzle clogging during casting. However, if it is contained in excess, it promotes the generation of spatter during welding. For this reason, the Ca content is set to 0.0025% or less. The Ca content is preferably set to 0.0020% or less, and more preferably set to 0.0015% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably set to 0.0010% or more.
[0035] Mg: 0.0100% or less Mg (magnesium) is an element that constitutes MgO. However, if Mg is contained in excess, inclusions are likely to be formed excessively, which is one of the causes of deterioration of characteristics. For this reason, the Mg content is set to 0.0100% or less, and preferably 0.0030% or less. On the other hand, in order to obtain the above effects, the Mg content is preferably set to 0.0001% or more, and more preferably 0.0005% or more.
[0036] In addition to the above elements, one or more elements selected from REM and Ta may be contained within the ranges shown below. The reasons for limiting the amount of each element will be explained below.
[0037] REM: 0~0.01% REM (Rare-Earth Metal) has a high affinity with O, so it has the effect of reducing the amount of MgO·Al2O3 spinel that causes nozzle clogging. In addition, because it has a high affinity with S, it improves hot workability by fixing S. For this reason, it may be contained as necessary. However, if REM is contained in excess, nozzle clogging due to REM oxides is likely to occur. Therefore, the REM content is set to 0.01% or less. The REM content is preferably set to 0.009% or less. On the other hand, in order to obtain the above effect, the REM content is preferably set to 0.0005% or more.
[0038] Here, REM refers to a total of 17 elements, including Sc, Y and lanthanides, and the above REM content means the total content of these elements. In industry, REM is often added in the form of misch metal.
[0039] Ta: 0 to 0.10% Ta (tantalum) has a high affinity with O, and therefore has the effect of reducing the amount of MgO·Al2O3 spinel that causes nozzle clogging. For this reason, it may be contained as necessary. However, excessive Ta content leads to a decrease in room temperature ductility and toughness. Therefore, the Ta content is set to 0.10% or less. The Ta content is preferably set to 0.08% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably set to 0.001% or more.
[0040] In addition to the above elements, one or more elements selected from B, W, V, Ti, Nb, Sn, Sb, Co, Zr, and Ga may be contained within the ranges shown below. The reasons for limiting each element will be explained.
[0041] B: 0~0.0020% B (boron) is an element that increases the strength of grain boundaries and has the effect of improving workability. Therefore, it may be contained as necessary. However, if B is contained in excess, it causes a decrease in ductility and decreases workability. Therefore, the B content is set to 0.0020% or less, and preferably 0.0010% or less. On the other hand, in order to obtain the above effect, the B content is preferably set to 0.0001% or more, and more preferably 0.0005% or more.
[0042] W: 0~2.0% W (tungsten) has the effect of further increasing corrosion resistance. Therefore, it may be contained as necessary. However, W is a very expensive element, and even if it is contained in excess, the effect is not worth the increase in alloy cost. Therefore, the W content is set to 2.0% or less. The W content is preferably set to 1.0% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.05% or more, and more preferably set to 0.25% or more.
[0043] V: 0~1.00% V (vanadium) has the effect of enhancing corrosion resistance. It is also an element that affects the ferrite phase ratio, and may be contained as necessary to adjust the DF value described later. However, if an excessive amount of V is contained, the toughness decreases. Therefore, the V content is set to 1.00% or less. The V content is preferably set to 0.20% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.01% or more, and more preferably set to 0.10% or more.
[0044] Ti: 0 to 0.005% Ti (titanium) is an element that affects the ferrite phase ratio, and may be included as necessary to adjust the DF value described later. However, if Ti is included in excess, TiN is generated before casting, which promotes nozzle clogging. Therefore, the Ti content is set to 0.005% or less. On the other hand, in order to obtain the above effect, the Ti content is preferably set to 0.001% or more.
[0045] Nb: 0 to 0.10% Nb (niobium) has the effect of improving formability and corrosion resistance. Therefore, it may be contained as necessary. However, if an excessive amount of Nb is contained, toughness decreases. Therefore, the Nb content is set to 0.10% or less, and preferably to 0.05% or less. On the other hand, in order to obtain the above effect, the Nb content is preferably set to 0.02% or more.
[0046] Sn: 0 to 0.10% Sn (tin) has the effect of further increasing corrosion resistance. Therefore, it may be contained as necessary. However, if an excessive amount of Sn is contained, toughness decreases. Therefore, the Sn content is set to 0.10% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably set to 0.02% or more.
[0047] Sb: 0 to 0.30% Sb (antimony) has the effect of further enhancing corrosion resistance. Therefore, it may be contained as necessary. However, if Sb is contained in excess, it may promote the formation of TiN, which may cause surface defects. Therefore, the Sb content is set to 0.30% or less, and preferably 0.10% or less. On the other hand, in order to obtain the above effect, the Sb content is preferably set to 0.01% or more.
[0048] Co: 0 to 1.00% Co (cobalt) has the effect of further enhancing corrosion resistance. Therefore, it may be contained as necessary. However, Co is a very expensive element, and if it is contained in excess, the alloy cost increases and the effect saturates. Therefore, the Co content is set to 1.00% or less. The Co content is preferably set to 0.80% or less. On the other hand, in order to obtain the above effect, the Co content is preferably set to 0.07% or more, more preferably set to 0.10% or more, and even more preferably set to 0.25% or more.
[0049] Zr: 0 to 0.0050% Zr (zirconium) has the effect of fixing S and can improve corrosion resistance and hot workability. Therefore, it may be contained as necessary. However, Zr has a very high affinity with S, and if contained in excess, it forms coarse sulfides in the molten steel, which actually reduces corrosion resistance. Therefore, the Zr content is set to 0.0050% or less. The Zr content is preferably set to 0.0040% or less. On the other hand, in order to obtain the above effects, the Zr content is preferably set to 0.0001% or more.
[0050] Ga: 0 to 0.01% Ga (gallium) has the effect of increasing corrosion resistance. Therefore, it may be contained as necessary. However, excessive content increases the alloy cost. Therefore, the Ga content is set to 0.01% or less. The Ga content is preferably set to 0.005% or less. On the other hand, in order to obtain the above effect, the Ga content is preferably set to 0.0001% or more.
[0051] In the chemical composition of this embodiment, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel, and are permissible within a range that does not adversely affect this embodiment.
[0052] 2. DF value: 20~60% In the steel wire rod of this embodiment, the DF value is controlled to be within a predetermined range. The DF value is a numerical value that is an index of the amount of ferrite phase in steel, and is calculated by the following formula (i). Note that formula (i) is calculated by regressing the relationship between the amount of ferrite phase obtained when manufacturing the steel by changing the composition range of various elements and the content of each element.
[0053] If the DF value is less than 20%, the amount of ferrite phase cannot be sufficiently secured, and the hot workability is deteriorated. Therefore, the DF value is set to 20% or more, and preferably to 30% or more. On the other hand, if the DF value exceeds 60%, the hot workability is deteriorated. Therefore, the DF value is set to 60% or less, and preferably to 55% or less.
[0054] DF value=7.2×(Cr+0.88Mo+0.78Si+2.2Ti+2.3V)-8.9×(Ni+0.03Mn+0.72Cu+22C+21N)-44.9 (i) In the formula (i), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the value is set to zero.
[0055] 3.Inclusions 3-1.Ca-Al-Mg oxide The duplex stainless steel wire rod according to the present embodiment has inclusions having a major axis of 1 μm or more and containing one or more selected from S and O. Among these inclusions, oxides that contain CaO, Al2O3, and MgO, the total of which satisfies the following formula (ii) and the ratio of Al2O3 to MgO satisfies the following formula (iii), are defined as Ca-Al-Mg-based oxides.
[0056] CaO+Al2O3+MgO+ROx+Ta2O5≧90% (ii) Al2O3 / MgO≦1.25 (iii) In addition, ROx in formula (ii) represents REM oxides, and CaO, Al2O3, MgO, ROx, and Ta2O5 in formulas (ii) and (iii) represent the mass percentage of each oxide, and are set to zero if not contained.
[0057] In the steel wire rod of this embodiment, the Ca-Al-Mg oxides are actively formed. Here, the Ca-Al-Mg oxides are oxides that satisfy the formula (ii), that is, the total amount of CaO, Al2O3, MgO, ROx, and Ta2O5 is 90% or more by mass. If the formula (ii) is not satisfied, it indicates the presence of a large amount of lower oxides such as SiO2 and MnO, which is undesirable because it is an oxide that leads to the generation of surface defects and internal defects during processing. Usually, Ca-Al-Mg oxides are often composed of oxides of Ca, Al, and Mg, but when REM, Ta, etc. are contained, for example, the oxides of REM (RO X), and / or oxides of Ta. This is because REM and oxides of Ta are generally unlikely to contribute to the generation of defects as described above. S may also be included.
[0058] In addition, the Ca-Al-Mg oxides satisfy formula (iii), that is, the ratio of Al2O3 to MgO is 1.25 or less. If the ratio of Al2O3 to MgO is 1.25 or less, MgO is more likely to form as a crystallized phase during continuous casting than MgO·Al2O3 spinel.
[0059] 3-2.Ca-Al-Mg oxide fraction The number ratio of Ca-Al-Mg oxides to the above-mentioned inclusions is 75% or more. If the number ratio of Ca-Al-Mg oxides is less than 75%, it will be a crystallized phase mainly composed of MgO, but MgO·Al 2 O 3) The nozzle is easily clogged due to the formation of a crystallized phase mainly composed of spinel. The number ratio of Ca-Al-Mg oxides is preferably 85% or more, and more preferably 90% or more.
[0060] 3-3. Observation of Ca-Al-Mg oxides and measurement of their number ratio The cross section of the steel wire rod perpendicular to the drawing direction is used as the observation surface, and is polished to a mirror finish. The observation surface is analyzed by SEM-EDS, and 100 or more inclusions with a major axis of 1 μm or more and containing O and / or S are randomly selected. This is used as a population, and the elements contained in the compounds of the population are analyzed by SEM-EDS. In this case, inclusions containing O and / or S and satisfying the requirements of the above formulas (ii) and (iii) are determined to be Ca-Al-Mg-based oxides. In this case, the content of each element in the inclusions is specified, and the specified elemental analysis values are used to determine the CaO, Al2O3, and MgO contents (mass%) in the oxide, assuming that Ca, Al, and Mg are all CaO, Al2O3, and MgO. In addition, if it is determined to be a Ca-Al-Mg-based oxide, the ratio of the 100 inclusions to the population is calculated as the number ratio (%) of Ca-Al-Mg-based oxides.
[0061] In addition, in JIS G 0555:2020, which is used as a general evaluation method for inclusions, even if two or more inclusions are present at a distance from each other, they may be regarded as one inclusion depending on the type and distance, but in this embodiment, they are regarded as individual inclusions. Also, the major axis of an inclusion refers to the length of the longest straight line when connecting two points on the periphery of the inclusion.
[0062] The reason for using a cross section perpendicular to the wiredrawing direction for observation is that the size in the direction parallel to the wiredrawing direction is significantly affected by the reduction rate and is therefore difficult to assess consistently, whereas the size in the direction perpendicular to the wiredrawing direction does not change significantly with rolling. Therefore, it is believed that the size of the major axis of the inclusions in the cross section perpendicular to the wiredrawing direction reflects the results of inclusion (oxide) control in the steelmaking stage, which is the key point of this embodiment. This is also true when the steel wire is made by wiredrawing.
[0063] 4. Steel Wire The steel wire is obtained by subjecting the above-mentioned steel wire material to wire drawing or the like. The steel wire also inherits the properties of the above-mentioned steel wire material, specifically, the properties such as the chemical composition and the number ratio of Ca-Al-Mg-based oxides. Therefore, if the steel wire also satisfies the chemical composition and the number ratio of Ca-Al-Mg-based oxides of the steel wire material of the present embodiment, it can be assumed that the steel wire is made of the steel wire material of the present embodiment.
[0064] 5.Applications The steel wire material and steel wire according to the present embodiment are suitable for use as welding materials such as welding rods.
[0065] 6. Manufacturing method A preferred method for producing the duplex stainless steel wire rod and the duplex stainless steel wire according to the present embodiment will be described. The duplex stainless steel wire rod and the duplex stainless steel wire according to the present embodiment can be stably produced, for example, by the following production method.
[0066] First, it is preferable to melt a main raw material such as iron ore and perform primary refining. The conditions of melting and primary refining are not particularly limited. They may be made according to a conventional method. Then, it is preferable to perform secondary refining. In the steel wire rod of this embodiment, Al is used as a deoxidizing agent to obtain the above-mentioned chemical composition of the steel wire rod. At this time, it is preferable to charge Al into the molten steel in two separate times. A specific description will be given below. At the beginning of the secondary refining, the first charge of Al is made and a deoxidation treatment is performed. By carrying out this deoxidation treatment, it is preferable to make the O concentration in the molten steel 0.006% or less. In addition, at this time, prior to the first charge of Al, preliminary deoxidation may be performed with Si, Mn, or the like, as necessary.
[0067] In order to minimize the crystallization of MgO·Al2O3 spinel during casting and to control the crystallization to MgO as the main product, it is necessary to increase the Mg concentration relative to the Al concentration in the molten steel, because this makes MgO stable and makes it difficult for MgO·Al2O3 spinel to form.
[0068] Therefore, in order to increase the Mg concentration in the molten steel and form the Ca-Al-Mg oxides so that the number ratio satisfies the range of this embodiment, it is preferable to increase the activity of MgO in the slag while decreasing the activity of Al2O3. Specifically, the activity of MgO is preferably 0.9 or more based on pure solid MgO, and the activity of Al2O3 is preferably 0.05 or less based on pure solid Al2O3.
[0069] In this case, the activities of MgO and Al2O3 in the slag may be calculated by measuring the composition of the slag and using a thermodynamic data collection and a commercial thermodynamic calculation software. If the activities of MgO and Al2O3 in the slag do not satisfy the above-mentioned range, the activities may be adjusted by the following method. In order to increase the activity of MgO, for example, it is preferable to add CaO and / or MgO to the molten steel. In addition, in order to decrease the activity of Al2O3, it is preferable to add CaO to the molten steel, for example.
[0070] In addition, in order to increase the Mg concentration in the molten steel, a method such as adding an Mg alloy or adding Ti can be considered, but it becomes difficult to adjust the chemical composition within the range of this embodiment, and nozzle clogging is likely to occur. For this reason, as described above, it is preferable to set the activities of MgO and Al2O3 in the slag to the above range. As a result, the Mg concentration in the molten steel can be stably increased and the Ca-Al-Mg oxide required in this embodiment can be sufficiently formed. Next, in the latter half of the secondary refining, it is preferable to add Al for the second time and adjust the components in the molten steel. In addition, other than the above conditions, the conditions of the secondary refining are not particularly limited. It is sufficient to follow a conventional method and adjust the range of the chemical composition of the steel wire rod of this embodiment.
[0071] The molten steel thus obtained is preferably continuously cast into a steel slab. The steel slab thus obtained is preferably heated, for example, in the range of 1000 to 1300°C, and hot-rolled. The rolling end temperature is preferably, for example, in the range of 900 to 1100°C, and the total area reduction is preferably 90.0% or more. After this hot rolling, a steel wire having a metal structure of duplex stainless steel is obtained. The diameter of the steel wire is not particularly limited, but is usually preferably in the range of 5.0 to 6.0 mm. Annealing, pickling, etc. may be performed as appropriate.
[0072] The obtained steel wire is preferably subjected to wire drawing to obtain a steel wire. The wire drawing may be performed multiple times, and heat treatment may be performed during the wire drawing, if necessary. The heat treatment temperature is preferably in the range of 1000 to 1100°C, for example, and it is sufficient that the structure of the duplex stainless steel is obtained after the heat treatment. In addition, pickling or the like may be performed as appropriate. The diameter of the steel wire is not particularly limited, but is usually preferably in the range of 0.5 to 1.5 mm.
[0073] Hereinafter, the steel wire material and the steel wire according to the present embodiment will be described more specifically with reference to examples, but the present embodiment is not limited to these examples. EXAMPLES
[0074] Molten steel having the chemical composition shown in Table 1 was poured into a tundish and cast into a cast piece using a mold. When producing the molten steel, deoxidation was performed with Al in the secondary refining. At this time, Al was charged in two separate times, and after the first Al charge, the O concentration in the molten steel was adjusted to 0.006% or less, and then the slag composition was controlled to adjust the activities of MgO and Al2O3 in the slag. Here, the activities in the slag in each example are as shown in Table 2 described later, and the activities in the table were calculated using thermodynamic calculation software on a pure solid basis. Then, the second charge of Al was performed. The chemical compositions in Table 1 are the chemical compositions after the adjustment of the component ranges of each element was completely completed.
[0075] [Table 1]
[0076] The obtained slab was heated to 1100°C and hot rolled under the conditions of a rolling start temperature of 1080°C, a rolling end temperature of 1050°C, and a total area reduction rate of 99.9%, to produce a steel wire rod with a wire diameter of 5.5 mm. Next, the obtained steel wire rod was subjected to a primary wire drawing process, followed by a strand heat treatment at 1000 to 1100°C, and then a secondary wire drawing process to produce a duplex stainless steel wire with a wire diameter of 1.0 mm.
[0077] The susceptibility to nozzle clogging during the manufacturing process, hot workability, and welding workability when welding was performed using a steel wire as a welding material were evaluated according to the following procedures.
[0078] (Nozzle blockage) Nozzle clogging during casting was judged based on whether the inner wall of the nozzle was clogged after casting. If the casting was completed, it was rated as good, and if there was no tendency for clogging, it was rated as excellent. On the other hand, if the nozzle was clogged and problems such as the inability to perform continuous casting occurred, it was rated as poor.
[0079] (Hot workability) The hot workability was evaluated as good when there were no surface defects on the steel wire rod after hot rolling, and was recorded as "good" when there were no defects. On the other hand, when there were surface defects with a depth of 0.15 mm or more, the hot workability was evaluated as poor and recorded as "poor."
[0080] (Welding workability) The welding workability was evaluated based on the presence or absence of spatter generation during welding. Specifically, a weld bead was produced in a copper collection box on a duplex stainless steel plate (NSSC2120, manufactured by Nippon Steel Stainless Steel Co., Ltd.) in a bead-on-plate manner for 1 minute using a welding rod made of the steel wire to be tested. The test conditions were a welding current of 150A, a voltage of 24V, a welding speed of 30cm / min, a shielding gas of 100% CO2 (20l / min), and no preheating. When no spatter was generated in the box during the production of the weld bead, the welding workability was evaluated as good and recorded as good. On the other hand, when spatter was generated, the welding workability was evaluated as poor and recorded as poor. The results are summarized in Table 2 below.
[0081] [Table 2]
[0082] As shown in Table 2, the samples B1 to B15 satisfied the requirements of the chemical composition and Ca-Al-Mg oxides of this embodiment, and therefore did not cause nozzle clogging, and had good hot workability and welding workability. On the other hand, the samples b1 to 8 did not satisfy at least one of the requirements of the chemical composition and Ca-Al-Mg oxides of this embodiment. As a result, at least one of the following problems occurred: nozzle clogging, deterioration of hot workability, and deterioration of welding workability.
[0083] In the case of b1, the activity of MgO was low, so the requirements for Ca-Al-Mg oxides were not met, and nozzle clogging occurred. In the case of b2, the activity of Al2O3 was high, so the requirements for Ca-Al-Mg oxides were not met, and nozzle clogging occurred.
[0084] The steel wire b3 had poor hot workability due to its low DF value. When the weldability was evaluated using the steel wire, spattering occurred due to the high Ca content. The steel wire b4 had poor hot workability due to its high S concentration. The steel wire b4 also had high O concentration, which resulted in high SiO2 and MnO concentrations, which did not satisfy the requirements for Ca-Al-Mg oxides. However, the amount of MgO·Al2O3 spinel, which causes nozzle clogging, was low, so nozzle clogging did not occur.
[0085] The specimen b5 had a low DF value, which resulted in poor hot workability. The specimen b6 had a high Al2O3 activity, which did not satisfy the requirements for the Ca-Al-Mg oxides of this embodiment, which resulted in nozzle clogging. The specimens b7 and b8 had low MgO activity or high Al2O3 activity, which did not satisfy the requirements for the Ca-Al-Mg oxides of this embodiment, which resulted in nozzle clogging.
Claims
1. A duplex stainless steel wire having inclusions having a major axis of 1 μm or more and containing one or more types selected from S and O in a cross section perpendicular to the wiredrawing direction, The chemical composition, in mass%, is C: 0.005-0.10%, Si: 0.2-2.0%, Mn: 0.1 to 6.0%, P: 0.04% or less, S: 0.0050% or less, Ni: 2.0 to 14.0%, Cr: 18.0-28.0%, Mo: 0.05-5.50%, Cu: 0.05-2.0%, N: 0.10-0.35%, O: 0.0001 to 0.0060%, Al: 0.010-0.2%, Ca: 0.0003-0.0025%, Mg: 0.0001-0.0100%, REM: 0-0.01%, Ta: 0-0.10%, B: 0 to 0.0020%, W: 0 to 2.0%, V: 0-1.00%, Ti: 0 to 0.005%, Nb: 0 to 0.10%, Sn: 0 to 0.10%, Sb: 0 to 0.30%, Co: 0-1.00%, Zr: 0 to 0.0050%, Ga: 0-0.01%, The balance is Fe and impurities. The DF value calculated by the following formula (i) is 20 to 60%, The inclusions are subjected to elemental analysis, and the Ca, Al and Mg identified are CaO, Al 2 O 3 and MgO, respectively. 2 O 3 and MgO, the total of which satisfies the following formula (ii), and Al 2 O 3 When an oxide in which the ratio of Ca to MgO satisfies the following formula (iii), is defined as a Ca-Al-Mg-based oxide, A duplex stainless steel wire rod, wherein the ratio of the number of the Ca-Al-Mg-based oxides to the number of the inclusions is 75% or more. DF value=7.2×(Cr+0.88Mo+0.78Si+2.2Ti+2.3V)-8.9×(Ni+0.03Mn+0.72Cu+22C+21N)-44.9...(i) CaO+Al 2 Oh 3 +MO+RO8+Ta 2 Oh 5 ≧90% ・・・(ii) Al 2 O 3 / MOO≦1.25 ・・・(iii) In formula (i), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero. In formula (ii), ROx represents REM oxides, and in formulas (ii) and (iii), CaO, Al 2 O 3 , MgO, ROx, Ta 2 O 5 indicates the mass percentage of each oxide, and if not contained, it is set to zero.
2. The chemical composition, in mass%, REM: 0.0005-0.01%, Ta: 0.001 to 0.10%, B: 0.0001 to 0.0020%, W: 0.05-2.0%, V: 0.01-1.00%, Ti: 0.001 to 0.005%, Nb: 0.02-0.10%, Sn: 0.02 to 0.10%, Sb: 0.01 to 0.30%, Co: 0.07-1.00%, Zr: 0.0001 to 0.0050%, and Ga: 0.0001-0.01%, The duplex stainless steel wire rod according to claim 1, comprising one or more selected from the group consisting of:
3. The duplex stainless steel wire rod according to claim 1 or 2, which is used as a welding material.
4. A duplex stainless steel wire using the duplex stainless steel wire rod according to claim 1 or 2.
Citation Information
Patent Citations
Duplex stainless steel, and method for producing the same
JP2009007638A
Two-phase stainless steel wire material for weld rod and two-phase stainless steel wire for weld rod
JP2018171640A
AUSTENITIC STAINLESS STEEL WITH HIGH CONTENT OF Si, HAVING EXCELLENT MANUFACTURABILITY
JP2019178363A
Boron-containing stainless steel having excellent hot workability and excellent surface properties
WO2013027253A1
Stainless steel, stainless steel material, and stainless steel production method
WO2021172378A1